Fabrication and characterization of poly(vinyl alcohol)-TiO2 nanocomposite films for orthopedic applications. (October 2016) - Mohanapriya, S.; Mumjitha, M.; PurnaSai, K.; Raj, V.
Abstract: Poly(vinyl alcohol) (PVA) is reinforced with TiO2 nanoparticles in order to enhance thermo-mechanical stabilities, surface characteristics and osteoblastic cell adhesion. PVA–TiO2 nanocomposite films with desirable mechanical, thermal and biocompatible properties are fabricated through solution casting method followed by de-hydrothermal cross-linking treatment. The composition of TiO2 nanoparticles was standardized to achieve mechanically stable nanocomposite films, based on tensile strength measurements composition of TiO2 is determined as optimal at 3 wt%. PVA–TiO2 nanocomposite films were characterized by Scanning electron microscopy, Energy dispersive spectroscopy, Atomic force microscopy, Ultra violet and Fourier transform infrared spectroscopic techniques. Elemental mapping studies substantiate incorporation of TiO2 nanoparticles within the PVA matrix. Dimensional stability evaluated by soaking films in SBF for 24 h insinuates the role of TiO2 in the direction of controlling degree of swelling. In-vitro bioactivity test and cell adhesion results also predict that presence of TiO2 is advantageous to enhance apatite growth and promote cell-substrate interaction. SEM studies illustrate improved surface morphology of PVA–TiO2 nanocomposite film with homogenously distributed TiO2 nanoparticles, which help to enhance thermo-mechanical behavior. TiO2 nanoparticles construct cell-adhesive hydrophilic nano-domains that act as potential cell adhesion sites and promotes osteointegration. Bio compatibility studies proved that thermally cross-linked PVA is non-toxic in relation to PVA cross-linked with glutaraldehyde. Cytotoxicity and cell adhesion of nanocomposite films evaluated through cell viability (MMT) assay and crystal violet staining revealed that PVA-3 wt% TiO2 nanocomposite could act as an excellent composite and hence suitable to be used in bone implant applications. Graphical abstract: Highlights: Poly vinyl alcohol is reinforced with TiO2 nanoparticles. TiO2 enhances stability and controls degree of swelling. Thermally cross-linked PVA present low /no cytotoxicity. Hydrophilic nanodomains created by TiO2 particles. Improved cell-substrate interaction.